2014
DOI: 10.1016/j.nucmedbio.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of [11C]PyrATP-1, a novel radiotracer for PET imaging of glycogen synthase kinase-3β (GSK-3β)

Abstract: Introduction The dysfunction of glycogen synthase kinase-3β(GSK-3β) has been implicated in a number of diseases, including Alzheimer’s disease. The ability to non-invasively quantify GSK-3βactivity in vivo is therefore of critical importance, and this work is focused upon development of inhibitors of GSK-3βradiolabeled with carbon-11 to examine quantification of the enzyme using positron emission tomography (PET) imaging. Methods [11C]PyrATP-1 was prepared from the corresponding desmethyl-piperazine precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…26 The radiotracer also exhibited poor brain uptake in rodent and primate brain with moderate increase in uptake during pretreatment with cyclosporine. 26,27 [ 11 C]SB-216763 ( K i = 9 nM) penetrates the BBB in mice and baboon, but shows homogeneous distribution. 28–30 In vivo evaluation of a series of [ 11 C]labeled oxindole analogues (IC 50 = 66–35 nM) also was proven unsuccessful in normal and cold water stress (CWS)-induced tau hyperphosphorylation mice model.…”
Section: Introductionmentioning
confidence: 99%
“…26 The radiotracer also exhibited poor brain uptake in rodent and primate brain with moderate increase in uptake during pretreatment with cyclosporine. 26,27 [ 11 C]SB-216763 ( K i = 9 nM) penetrates the BBB in mice and baboon, but shows homogeneous distribution. 28–30 In vivo evaluation of a series of [ 11 C]labeled oxindole analogues (IC 50 = 66–35 nM) also was proven unsuccessful in normal and cold water stress (CWS)-induced tau hyperphosphorylation mice model.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 C]SB-216763 showed good brain uptake in rodents and non-human primates (NHPs) but was not selective against other structurally similar kinases. [11] [ 11 C]PyrATP-1 [12] and 11 C-oxadiazole [13] -based radiotracers failed to show appreciable uptake in vivo.N one of the PET radiotracers for GSK-3 has yet proven to be successful for in vivo imaging studies with specificity and/or suitable brain uptake ( Figure 1). Thus an acute need for PET neuroimaging of GSK-3 remains, specifically for clinical research applications in AD and non-AD tauopathies.…”
mentioning
confidence: 99%
“…As a result, [ 11 C]AR‐A014418 showed markedly low levels of radioactivity in all brain regions, indicating that this PET imaging probe cannot be used for the in vivo detection of GSK‐3β. Thereafter, Cole et al reported on the synthesis and evaluation of [ 11 C]PyrATP‐1, which is a 11 C‐labeled GSK‐3β inhibitor based on the pyrazine scaffold . Similarly to [ 11 C]AR‐A014418, the poor brain uptake of [ 11 C]PyrATP‐1 revealed that it may be inappropriate for the quantification of GSK‐3β.…”
Section: Introductionmentioning
confidence: 99%